Diabetic Kidney Disease Position Paper of the Macedonian Society of Nephrology, Dialysis, Transplantation and Artificial Organs (MSNDTAO), Macedonian Society of Cardiology (MSC), and Scientific Association of Endocrinologists and Diabetologists of Macedonia (SAEDM) - Spasovski, Goce; Shterjova Markovska, Zhaklina; Kostov, Jorgo; Gjorgjievski, Nikola; Bosevski, Marijan; Poposka, Lidija; Ahmeti, Irfan; Jovanovska Mishevska, Sasha; Milenkovic Tatjana (Walter de Gruyter GmbH, 2024)
Diabetic kidney disease (DKD) is a significant and growing global health concern, affecting a substantial proportion of individuals with diabetes mellitus. This position paper of Scientific societies of endocrinologists, nephrologists and cardiologists has been consensually brought at a couple of mutual meetings, aiming to synthesize current knowledge on screening, diagnosis and staging of DKD, emphasizing the need for an early detection and intervention in order to prevent progression to end-stage renal disease (ESRD). The role of glycemic control, blood pressure management, lipid management and the use of reno and cardioprotective agents, including angiotensin-converting enzyme inhibitors, sodium-glucose co-transporter 2 inhibitors and non-steroidal mineralocorticisteroid receptor antagonist has been entirely considered. Furthermore, we highlight the importance of a multidisciplinary approach in the care of patients with DKD, integrating lifestyle modifications and patient education into the clinical practice. This paper advocates for the implementation of standardized screening protocols and the development of personalized treatment strategies to optimize patient outcomes. By addressing the complexities of DKD, we aim to provide a comprehensive framework for healthcare professionals to enhance the quality of care for individuals at risk of or living with this condition.
Keywords: Diabetic kidney disease; angiotensin-converting enzyme inhibitors; lifestyle modifications; non-steroidal mineralocorticosteroid receptor antagonist; sodium-glucose co-transporter 2 inhibitors